INFORMATION GAP TASKS: MOTIVATING AND ENCOURAGING TALK IN ENGLISH CLASSROOMS (Practitioner Research, 2022)
This study examines how the use of information gap tasks in an English language classroom promoted the use of wh-questions among learners and increased interaction among learners. Literature shows that there is a tendency for language teachers to control the patterns of classroom communication as well as control talk in the classroom, thus limiting interaction and talk among learners. In second language acquisition, learners need to interact in the target language as studies show that learners need to learn to talk and also talk to learn (Tsui, 1995; 2017). Questioning is an important pathway for learners to learn as well as create a talk to acquire language. This paper examines the use of information gap tasks to encourage and promote interaction via wh-questions among learners in a primary vernacular public school in Malaysia. The study adopts a mixed method approach to datacollection where pre-and post-tests were used to analyze the effects of information-gap tasks on wh-questions use. Interaction analysis was also done to examine how learners from different levels of proficiency interacted during the information-gap tasks. The findings of this study revealed that the use of information-gap tasks improved the learners’ use of interrogative pronouns in terms of constructing questions to obtain their desired answers as well as encouraging interactions. Information-gap tasks are suitable tasks and tools to be used in the language classroom to encourage talk and interaction amongst learners to aid language development.